PENGARUH BUDAYA ORGANSASI TERHADAP KINERJA KARYAWAN DI PERUSAHAAN - Yani Rahman Yuliansyah; Sri Yanthy Yosepha (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to determine the effect of organizational culture on employee performancein organization/company X. This research uses a literature review of some of the results ofprevious studies in Indonesia. Sources of journal searches via Google in the period 2017 –2019. The research results and discussion analysis prove that organizational culture andorganizational commitment are important factors that can explain variations in employeeperformance. Cultural values that are believed to be shared can become a bond between theorganization and employees. Thus, this strong bond can lead to employee motivation toimprove employee performance in completing work optimally.